2001
DOI: 10.1152/ajpcell.2001.280.6.c1669
|View full text |Cite
|
Sign up to set email alerts
|

Stress fiber organization regulated by MLCK and Rho-kinase in cultured human fibroblasts

Abstract: To understand the roles of Rho-kinase and myosin light chain kinase (MLCK) for the contraction and organization of stress fibers, we treated cultured human foreskin fibroblasts with several MLCK, Rho-kinase, or calmodulin inhibitors and analyzed F-actin organization in the cells. Some cells were transfected with green fluorescent protein (GFP)-labeled actin, and the effects of inhibitors were also studied in these living cells. The Rho-kinase inhibitors Y-27632 and HA1077 caused disassembly of stress fibers an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
203
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(236 citation statements)
references
References 24 publications
31
203
2
Order By: Relevance
“…To examine our proposed idea that the elongated FA affects the cytoskeleton development and arrangement in a tension-dependant manner, we used ML-7 to inhibit MLCK function and reduce cellular tension, while maintaining the central stress fiber structure and FA development (Fig. 4e lower panel) [40]. As a consequence, MLCK expression could be efficiently inhibited by 10 mM of ML-7 compared to the control group (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…To examine our proposed idea that the elongated FA affects the cytoskeleton development and arrangement in a tension-dependant manner, we used ML-7 to inhibit MLCK function and reduce cellular tension, while maintaining the central stress fiber structure and FA development (Fig. 4e lower panel) [40]. As a consequence, MLCK expression could be efficiently inhibited by 10 mM of ML-7 compared to the control group (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…A third reason may have to do with the pathways used for contraction. The ROCK system and the myosin regulatory light chain kinase system (MLCK) are two distinct pathways involved in contraction of NHFs (24,25). By blocking the ROCK pathway in NHFs, the MLCK pathway may compensate and mask the full effect of blocking contraction.…”
Section: Discussionmentioning
confidence: 99%
“…In neither case, however, has the motor mechanism responsible for translocation been identified. In fibroblasts and smooth muscle cells on planar surfaces, it has been reported that myosin phosphorylation and cell contractile activity can be independently stimulated by myosin light chain kinase and Rho kinase in different topographic regions of the cells (Totsukawa et al, 2000;Katoh et al, 2001;Miyazaki et al, 2002). Also, maturation of focal adhesions in size has been attributed in part to ␣-smooth muscle actin (Dugina et al, 2001).…”
Section: Discussionmentioning
confidence: 99%